Antimicrobial efficacy of octenidine hydrochloride and calcium hydroxide with and without a carrier: A broth dilution analysis - Vinaya Susan Varghese; Veerendra Uppin; Kishore Bhat; Madhu Pujar; Amruta B Hooli; Nirmal Kurian (Wolters Kluwer Medknow Publications, 2018)
Background: An efficient antimicrobial agent action is required for a predetermined time period for absolute elimination of root canal microbes. Till date, there is limited or no data on the antimicrobial effect of octenidine as an intracanal medicament with chitosan (CTS) as a carrier against Candida albicans and Enterococcus faecalis. Aim: The aim of this microbiological study was to compare the antimicrobial efficacy of octenidine hydrochloride (OHC) and calcium hydroxide (Ca[OH]2) as intracanal medicaments, both independently and along with CTS as a carrier molecule against the common resistant endodontic pathogens. Materials and Methods: A total of 160 single-rooted anterior teeth were selected, root canal preparation was done, and teeth were divided into two groups and contaminated with C. albicans and E. faecalis, which were further divided into four test groups each according to intracanal medicaments used. CTS was used as a vehicle for OHC and Ca(OH)2and antimicrobial assessment was performed on day 2 and day 7 following broth dilution method. Dentine samples were collected after each time interval, and the number of colony-forming units was determined. Results: All four medicaments used in this study showed antifungal and antibacterial activity that diminished from day 2 to day 7. Group I (OHC alone) and Group IV (Ca[OH]2alone) showed significant antimicrobial activity against C. albicans and E. faecalis, respectively, than the other groups. Conclusion: A combination of OHC + CTS and Ca(OH)2+ CTS produced inferior results than that of the medicaments used alone.